Structural basis for cold adaptation - Sequence, biochemical properties, and crystal structure of malate dehydrogenase from a psychrophile Aquaspirillium arcticum - Kim, SY; Hwang, KY; Kim, SH; Sung, HC; Han, YS; Cho, YJ (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 1999)
Aquaspillium arcticum is a psychrophilic bacterium that was isolated from arctic sediment and grows optimally at 4 degrees C, We have cloned, purified, and characterized malate dehydrogenase from A. arcticum (Aa MDH). We also have determined the crystal structures of apo-Aa MDH, Aa MDH.NADH binary complex, and Aa MDH.NAD.oxaloacetate ternary complex at 1.9-, 2.1-, and 2.5-Angstrom resolutions, respectively. The Aa MDH sequence is most closely related to the sequence of a thermophilic MDH from Thermus flavus (Tf MDH), showing 61% sequence identity and over 90% sequence similarity. Stability studies show that Aa MDH has a half-life of 10 min at 55 degrees C, whereas Tf MDH is fully active at 90 degrees C for 1 h. Aa MDH shows 2-3-fold higher catalytic efficiency compared with a mesophilic or a thermophilic MDH at the temperature range 4-10 degrees C. Structural comparison of Aa MDH and Tf MDH suggests that the increased relative flexibility of active site residues, favorable surface charge distribution for substrate and cofactor, and the reduced intersubunit ion pair interactions may be the major factors for the efficient catalytic activity of Aa MDH at low temperatures.
Keywords: ACTIVE CITRATE SYNTHASE; ESCHERICHIA-COLI; LACTATE-DEHYDROGENASE; ANTARCTIC BACTERIUM; RESOLUTION; ENZYMES; THERMOSTABILITY; PURIFICATION; EXPRESSION; STABILITY